Search for quark contact interactions in dijet angular distributions in pp collisions at root s=7 TeV measured with the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; Abramowicz, H; Abreu, H; Acerbi, E; Acharya, B; et al. (2011)
Dijet angular distributions from the first LHC pp collisions at center-of-mass energy s=7 TeV have been measured with the ATLAS detector. The dataset used for this analysis represents an integrated luminosity of 3.1 pb-1. Dijet Χ distributions and centrality ratios have been measured up to dijet masses of 2.8 TeV, and found to be in good agreement with Standard Model predictions. Analysis of the λ distributions excludes quark contact interactions with a compositeness scale Χ below 3.4 TeV, at 95% confidence level, significantly exceeding previous limits. © 2010 CERN.